(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2023)
This study aims to reduce heat gain and minimise cooling energy through building envelope material as a passive design intervention strategy to achieve thermal comfort. Integrated Learning Building in the Faculty of Engineering, Universitas Indonesia, is used as a case study due to its air conditioning setting. First, the material characteristic of the building envelope is calculated using the Overall Thermal Transmission Value (OTTV) calculation to determine heat gain and the EDGE (Excellence in Design for Greater Efficiencies), a software to estimate cooling energy consumption. Then, a passive design intervention strategy is performed by adding insulation (polyester, bagasse, and recycled textile and paper) and substituting window glazing (reflective, PVB laminated, and Clear IGU Low-E). The results show that the combination of recycled textile and paper insulation and clear IGU Low-E window glazing has an OTTV value of 24.89 W/m2 which is lower than the standard in Indonesia (35 W/m2). Meanwhile, the cooling energy usage shows an energy consumption of 1.14% lower, but it did not achieve the 5% reduction target. Therefore, further intervention on other parts of the building envelope, such as the roof and floor, should be observed to achieve higher energy-saving potential.